KORELASI ANTARA MOTIVASI BELAJAR DAN MINAT BELAJAR DENGAN HASIL BELAJAR SISWA KELAS V SD - Ester Ester; Siti Halidjah; Suparjan Suparjan (Universitas Tanjungpura, 2021)
AbstractThis study is to describe whether or not there is a correlation between learningmotivation and interest in learning with student learning outcomes in the thematic learningof class V Elementary School 16 North Pontianak. The research method used is adescriptive method in the form of relationship studies by using correlation studies. Thepopulation in this study amounted to 81 students and the samples used were all students ofclass V, which amounted to 81 students. The data collection techniques in this research aredirect communication techniques, indirect communication techniques and documentarystudy techniques. As for the instrument (data collection tool) of this study in the form ofinterviews (interviews), questionnaires (questionnaires) and documents from the theme 1test. While the results of the theme 1 test of the fifth grade students of the State ElementarySchool 16 North Pontianak obtained an average of 89.50 in the